Drivers of Interspecific Spatial Segregation in Two Closely-Related Seabird Species at a Pan-Atlantic Scale - Bonnet-Lebrun, Anne-Sophie; Matthiopoulos, Jason; Lemaire-Patin, Rémi; Deville, Tanguy; Barrett, Robert; Bogdanova, Maria I.; Bolton, Mark; Christensen-Dalsgaard, Signe; Daunt, Francis; Dehnhard, Nina; Descamps, Sebastien; Elliot, Kyle; et al. (Journal of Biogeography, 2024)
Aim - Ecologically similar species living in sympatry are expected to segregate to reduce the effects of competition where resources are limiting. Segregation from heterospecifics commonly occurs in space, but it is often unknown whether such segregation has underlying environmental causes. Indeed, species could segregate because of different fundamental environmental requirements (i.e., ‘niche divergence’), because competitive exclusion at sympatric sites can force species to either change the habitat use they would have at allopatric sites (i.e., ‘niche displacement’) or to avoid certain areas, independently of habitat (i.e., ‘spatial avoidance’). Testing these hypotheses requires the comparison between sympatric and allopatric sites. Understanding the competitive mechanisms that underlie patterns of spatial segregation could improve predictions of species responses to environmental change, as competition might exacerbate the effects of environmental change. Location - North Atlantic and Arctic. Taxa - Common guillemots Uria aalge and Brünnich's guillemots Uria lomvia. Methods - Here, we examine support for these explanations for spatial segregation in two closely-related seabird species, common guillemots (Uria aalge) and Brünnich's guillemots (U. lomvia). For this, we collated a pan-Atlantic data set of breeding season foraging tracks from 1046 individuals, collected from 20 colonies (8 sympatric and 12 allopatric). These were analysed with habitat models in a spatially transferable framework to compare habitat preferences between species at sympatric and allopatric sites. Results - We found no effect of the distribution of heterospecifics on local habitat preferences of the focal species. We found differences in habitat preferences between species, but these were not sufficient to explain the observed levels of spatial segregation at sympatric sites. Main Conclusions - Assuming we did not omit any relevant environmental variables, these results suggest a mix of niche divergence and spatial avoidance ...